A study on prevalence and socio demographic factors associated with overweight and obesity among high school children of Raichur city - Fahim, M. A.; Ranjan, Din Prakash; Kirte, Rahul C. (International Journal Of Community Medicine And Public Health, 2023)
Background: Overweight/obesity among children is an emerging public health problem in our country. Overweight/obesity is a form of development-driven malnutrition that is emerging among all ages and socio-economic groups. Childhood overweight/obesity is a risk factor for later adult diseases and is associated with impaired health during childhood itself which may continue untreated for many years. The belief that overweight/obesity was the problem of developed countries alone is no longer true. India is one of the developing countries showing emerging and rising trends of overweight/obesity. Methods: A cross sectional study was undertaken in high schools of Raichur city. Data was collected by interviewing 1900 study subjects using pre-tested semi-structured questionnaire and by physical examination. The data was analyzed using percentages, proportions, odds ratio and Chi-square test with the help of Epi Info 7 software. Results: Prevalence of overweight and obesity among high school children of Raichur city was found to be 4.57% and 5.11% respectively. Significant association of overweight/obesity was found with gender, age, religion, socio-economic status, parent’s education, type of diet and physical exercise. Conclusions: Considering association of overweight/obesity with various risk factors, preventive measures like lifestyle modifications, changes in dietary pattern and regular exercise should be promoted in these age group children.